Values of Religus Character Education in the Story of Che' Anggun Tunggal - Muhammad Haidar Al Aziz (Budapest International Research and Critics University, 2022)
This paper aims to describe and analyze the values of religious character education contained in the saga Che' Anggun Tunggal. The research method used is a qualitative method with a descriptive approach. The data collection technique used is the documentation technique. While the analytical technique used in this study is the interactive analysis technique of Miles & Huberman. The results of this study indicate that the value of religious character education in the content of the saga Che' Anggun Tunggal is manifested in three dimensions, namely: the dimensions of belief (ideological), practice (ritualistic), and appreciation (experiential). In the dimension of belief, religious character is manifested in the form of belief in God's destiny (qadha' and qadar), belief in the qadim of Allah, and belief in the existence of Allah. As for the dimension of religious experience, religious character is manifested through marriage rituals. While in the dimension of religious experience, religious character is manifested through the expression of gratitude.